Preparing previously COVID-19-positive patients for elective surgery: a framework for preoperative evaluation - Bui, Naomi (Perioper Med (Lond), 2021)
The preoperative evaluation and risk assessment has always been a critical aspect of safe surgical practice, and in the midst of the SARS-CoV-2 pandemic, it has become even more crucial to patient safety. Emerging data show that surgical procedures in patients who test positive for coronavirus disease (COVID) are associated with worse clinical outcomes and increased postoperative complications and mortality. In addition to personal protective equipment (PPE) management, isolation protocols, preoperative SARS-CoV-2 screening, and steps to ensure clinician safety, determining how to deem patients who have recovered from COVID-19 safe to proceed is an added challenge. We present a preoperative protocol for evaluation of previously COVID-positive patients for elective surgery.